2003
DOI: 10.1177/135581960300800108
|View full text |Cite
|
Sign up to set email alerts
|

What Predicts Patients' Interest in the Internet as a Health Resource in Primary Care in England?

Abstract: Access, demographics and, particularly, motivational factors all influence patients' interest in the Internet as a health resource. Proposals to encourage more widespread use of digital health information need to take account of this complexity and not deal with access issues alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 12 publications
2
73
1
3
Order By: Relevance
“…Beyond a lack of perceived need reported by nearly 50% of respondents, these included a lack of confidence using online communities (30%), trust in Internet resources (24%), confidence using computers in general (20%), or awareness of online breast cancer communities (20%). These findings reflect many of the modifiable factors that have been shown to influence Internet use for health information more generally (e.g., a positive outcome expectancy, previous use of health websites, positive Internet self-efficacy) [38].…”
Section: Benefit Comparison Quotesupporting
confidence: 57%
“…Beyond a lack of perceived need reported by nearly 50% of respondents, these included a lack of confidence using online communities (30%), trust in Internet resources (24%), confidence using computers in general (20%), or awareness of online breast cancer communities (20%). These findings reflect many of the modifiable factors that have been shown to influence Internet use for health information more generally (e.g., a positive outcome expectancy, previous use of health websites, positive Internet self-efficacy) [38].…”
Section: Benefit Comparison Quotesupporting
confidence: 57%
“…Most studies concentrate on those who already have a computer. Older people from deprived areas tend not to have Internet access or do not see the need for it (Mead et al, 2003;Dutton et al, 2005). In this randomized controlled trial we provided new computers and a one-year broadband subscription to men and women medically diagnosed with coronary heart disease (CHD) and living in a derived area.…”
Section: Introductionmentioning
confidence: 99%
“…One major contributing factor in the individual's reported interest in obtaining health information from the Internet was their confidence in their ability to use the Internet -"self-efficacy" and "positive outcome expectancy". In other words, the belief that Internet use will help them deal with health concerns will encourage further use [18]. The fact that users consistently reported that the NSHN was easy to use increases the probability that they will return to the site for future health care information needs.…”
Section: Resultsmentioning
confidence: 99%
“…Internet surveys indicate that online information does directly influence users' decision making about health issues [18]. One survey indicated that more than 70% of users said that health information found online influenced a decision about their treatment [22].…”
Section: Resultsmentioning
confidence: 99%